Optimization of Making Charcoal Briquettes from Rice Husks with Variations in the Composition of Adhesive Materials and Compaction Pressure - Nada Hamdi; Indah; Riesto Atantio Fajri (Formosa Journal of Applied Sciences, 2023)
This study was done to find a way to turn the rice husk trash. This study aims to generate high-quality briquettes by optimizing the composition of adhesive materials and compaction pressure during the production of briquettes from rice husks. This study's methodology was an experimental one. Testing briquette quality involves measuring their moisture content (%), ash content (%), and calorific value (cal/g) in accordance with SNI 01-6235-2000, which is the standard for briquette quality. The conclusion is briquette samples with a 70:30 composition of charcoal and adhesive and high compaction pressure are the most ideal samples, as evidenced by the fact that they passed the moisture content test and created products with the lowest ash content and highest calorific value.